Method for Theoretical Assessment of Safety against Derailment of New Freight Wagons - Valeri Stoilov; Svetoslav Slavchev; Vladislav Maznichki; Sanel Purgic (Applied Sciences, 2023)
The assessment of safety against freight wagons’ derailment is a mandatory element of the documents provided to the EU notifying authorities of the entry into service of new freight wagons. The assessment methodology is presented in EN 14363:2019. It is mainly aimed at the experimental measurement of certain parameters, and the data are used to calculate the safety criterion. The practical implementation of the tests is accompanied by many difficulties: finding a track with a proper radius, ensuring free access to the railway infrastructure for a long period of time, waiting for suitable metrological conditions, preparing the curve and the test wagon, etc. These difficulties are well known to the European legislators, and as a solution, they propose a large set of reference wagons that have undergone real tests. It is sufficient to demonstrate that the parameters of the new wagon relate to some of the reference wagon parameters to avoid such a requirement. Proving the “convergence” of the parameters of the new and the reference wagons is a lengthy, complex, and, in many cases, subjective process. To introduce an objective assessment, the authors set themselves the task of developing a theoretical method to assess safety against derailment.